2005
DOI: 10.1021/om049188b
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Coupling of CO and Vinylidene LigandsFormation of Cyclobutane-1,3-diones

Abstract: Photolysis of pentacarbonyl vinylidene complexes of chromium and tungsten affords cyclobutane-1,3-dione derivatives, whereas thermolysis yields binuclear vinylidene nonacarbonyl complexes. In contrast to vinylidene complexes, photolysis of the diphenylallenylidene chromium complex gives, without incorporation of CO, the dimer of the allenylidene ligand, tetraphenylhexapentaene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…In our study it was observed that a bimolecular coupling of the tungstanorbornylidene intermediate species led to the formation of bi-(NBE) and regenerated the binuclear compound 1. A similar bimolecular coupling of two carbene ligands has been observed during mild thermolysis of chromium (0) and tungsten(0) pentacarbonylcarbene complexes [33][34][35] and detected by Schrock et al in reaction of alkylidene complexes of tantalum, molybdenum, and tungsten [36][37][38]. For the first time the carbene-carbene coupling reaction was applied in synthesis of bi-(NBE) from NBE in reaction catalyzed by a WASn compound [30].…”
Section: Reactivity Of Compound 1 Towards Norbornenesupporting
confidence: 52%
“…In our study it was observed that a bimolecular coupling of the tungstanorbornylidene intermediate species led to the formation of bi-(NBE) and regenerated the binuclear compound 1. A similar bimolecular coupling of two carbene ligands has been observed during mild thermolysis of chromium (0) and tungsten(0) pentacarbonylcarbene complexes [33][34][35] and detected by Schrock et al in reaction of alkylidene complexes of tantalum, molybdenum, and tungsten [36][37][38]. For the first time the carbene-carbene coupling reaction was applied in synthesis of bi-(NBE) from NBE in reaction catalyzed by a WASn compound [30].…”
Section: Reactivity Of Compound 1 Towards Norbornenesupporting
confidence: 52%
“…The first direct evidence for an alkene-to-alkylidene rearrangement was obtained by Wolczanski et al [19]. A bimolecular coupling of two carbene ligands and the formation of new olefin has been observed during mild thermolysis of chromium(0) and tungsten(0) pentacarbonylcarbene complexes [20][21][22] and detected by Schrock et al in reaction of alkylidene complexes of tantalum, molybdenum and tungsten [23][24][25]. For the first time the carbene-carbene coupling reaction was applied in synthesis of bi-NBE from NBE in reaction catalyzed by the binuclear compound 2 [4].…”
Section: Reactivity Of Compound 1 Towards Norbornenementioning
confidence: 99%
“…The transfer of a vinylidene ligand from manganese to rhenium and from rhodium to iridium has been described . In contrast to group 6 carbene complexes and to these vinylidene complexes the transfer of allenylidene ligands from chromium, molybdenum, and tungsten to another transition metal center has not been observed, although the thermal dimerization of the allenylidene ligand in [Cp(CO) 2 MnCCC( t -Bu) 2 ] and the photochemically induced dimerization of that in [(CO) 5 CrCCCPh 2 ] has been described. We now report the first examples of transmetalation of allenylidene ligands from chromium to tungsten.…”
Section: Introductionmentioning
confidence: 99%